Interpreting Thematic Relations Cyclically. (15th May 2013) - Fujii, Tomohiro
Abstract Defending the movement theory of control, Bowers (2008) suggests a possibility that thematic relations are interpreted in a cyclic manner. I argue that this conception of thematic interpretation enables the movement theory of control to respond to one existing empirical argument against it, which concerns cases where an argument apparently cannot raise from a non‐θ‐position to a θ‐position to allegedly satisfy the θ‐Criterion. The central proposal is that the problem does not arise if the θ‐Criterion is formulated to apply phase by phase to detect the thematic uninterpretability of the derivation in on‐line fashion. I also argue that the proposal allows us to further motivate the "equivalence of Merge and Move" thesis discussed by Chomsky (2004, 2005, 2008).